Validation of the generalized anxiety disorder screener (GAD-7) in Cypriot pregnant and postpartum women - Vogazianos, Paris; Motrico, Emma; Domínguez-Salas, Sara; Christoforou, Andri; Hadjigeorgiou, Eleni (My University, 2022)
Anxiety is increasingly acknowledged as a common mental health issue during the perinatal period. Its prevalence as well as the associated adverse effects constitute screening imperative. This study evaluates the psychometric properties and underlying factor structures of a Greek version of GAD-7 among pregnant and postpartum women (up to 6 months) in Cyprus.
Keywords: Anxiety; GAD-7; Perinatal anxiety; Postpartum; Pregnancy